The Influence of Travel Motivation on Satisfaction and Intention to Visit Terengganu - Mohammed Hazaea Hasan, Tewfik; Puad Mat Som, Ahmad; Ismail, Fathilah (International Journal of Engineering and Technology, 2018)
Tourism is considered one of the fundamental industries worldwide, which has the potential to strengthen economic development. In 2017 only, tourist comings to Malaysia generated a national income of RM49.6 billion. This study aims to determine whether tourists are gratified with their visit to Terengganu for tourism and to explore the factors influencing the tourist satisfaction by push and pull travel motivations. The touristsâ€™ perceptions are important since they could be used to determine the degree of their contribution to the development of tourism. The findings indicated that the overall tourist satisfaction with their visit to Terengganu is high, with a mean value of 3.84. The findings also showed that factors influencing the tourists to visit Terengganu are hospitality of the service providers, friendly attitude of the local communities, local culture, and attractive scenery. There is a need for concerted efforts to increase the touristsâ€™ satisfaction since it influences their intention for future visit to the state.Â Â Â